EFFECT OF THYROXINE ON HATCHING AND ON POSTEMBRYONIC GROWTH IN BRACHYDANIO RERIO, CYPRINUS CARPIO, LABEO ROHITA, DIRRHINA MRIGALA AND CATLA CATLA - SAWANT, N. H.; BELSARE, S. G. (Journal of Indian Fisheries Association, 2015)
Studies on the effect of thyroxine on the eggs and postembryonicgÂ·rowth of Brachydanio rerio, Cyprinus carpio, Labeo rohita, Cirrhinamrigala and Catla catla have been carried out. The treatments weregiven in the dosages ranging from 0.025 to 0.20 mg. Lower doses of0.025 to 0.075 mg were effective in reducing the hatching period,accelerating the yolk absorption and improving the growth ofpostembryonic s~ages in case of all the five species. Higher doses of0.15 to 0.20 mg were found to reduce the survival significantly in B.rerio,C. carpio, L. rohita and C.mrigala.